Hepatitis E: A rare cause of immune thrombocytopenic purpura (Indian Journal of Case Reports, 2020)
Acute viral hepatitis in children usually is a self-limiting mild disease which does not require any specific treatment. It is most commonly caused by hepatotropic viruses, hepatitis A and hepatitis E virus spread by the feco-oral route. Hepatitis E infection mostly follows an asymptomatic and anicteric course in the younger age group than icteric hepatitis. Rarely, they cause cholestatic hepatitis and fulminant hepatitis. It may rarely be associated with various extra-hepatic autoimmune manifestations. We herein report an extremely rare case of immune thrombocytopenia in a young girl associated with acute hepatitis E infection, who had an uneventful course on conservative management. She presented to us with nausea, vomiting, lethargy, jaundice, and petechial spots. On examination and investigating further, the patient had features of immune thrombocytopenic purpura and positive serology for IgM hepatitis E, whereas, a workup for other causes was normal.